Hypotension During Haemodialysis: Aetiology, Risk Factors and Outcome (Anwer Khan Modern Medical College Journal, 2017)
Background: Hypotension during hemodialysis is common. In some patients, the development of hypotension necessitates intravenous fluid replacement before patients are able to safely leave the dialysis unit. Intradialytic hypotension may reduce the efficacy of the dialysis procedure and contributes to the excessive morbidity and mortality that is associated with hemodialysis.Aims: The aim of the study is to identify the patients who develops intradialytic hypotension and find out the aetiology, risk factors and outcome to reduce the mortality and morbidity of those patients.Methodology: This Cross sectional descriptive type of observational study was conducted in the Haemodialysis Unit of Anwer Khan Modern Medical College Hospital over the period from January 2015 to December 2016. The change in systolic pressure during haemodialysis was reviewed for ten consecutive haemodialysis in all the patients. The patients with chronic renal failure who were on regular dialysis were enrolled. Patients with sepsis, hemoglobin level less than 9 g/dL, low cardiac output, acute coronary syndrome, significant valvular lesion or body weight below the dry weight of the patient were excluded from the study.Result: Ninetythree patients were included in the study. Among them male 53(56.98%) and female 40(43.02%) with a M:F ratio was 1.3:1. The mean age of the patients was 53.50±16.82 (Range 13- 90).We found that 28%(26) of the patients developed intradialytic hypotension at least once in consecutive ten dialysis. Out of them 14 were female and 12 patients were male. All of the patients recovered from the incident after adequate management and stoppage of the ultrafiltrate volume, convert the machine to SLED(Sustained low efficacy dialysis) mode and hold antihypertensive drugs morning dose on the day of haemodialysis and treatment of the cause.Conclusion: As a result of increasing age of the patients receiving hemodialysis and the increasing incidence of diabetic nephropathy, hypotension will become a greater problem in future.Anwer Khan Modern Medical College Journal Vol. 8, No. 2: Jul 2017, P 89-93